Breaking the Stigma: Increasing Comprehensive HIV Knowledge to End Discrimination Against People Living with HIV - Faid Nawawi; Adi Nugroho; Isabella Revina Wibowo (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Human Immunodeficiency Virus (HIV) is a virus that infects white blood cells and reduces human immunity. Meanwhile, acquired immune deficiency syndrome (AIDS) is a group of symptoms caused by HIV infection that result in decreased immunity. According to UNAIDS data, the estimated number of people living with HIV in Indonesia (2021) reach 540,000, with approximately 200,000 being women and girls, and 19,000 being children. In Indonesia, the HIV prevalence rate is 0.3%, with a total of 27,000 new infections each year. According to more complete data, up to 26,000 people living with HIV died of AIDS. When compared to ten years ago, the percentage of new infections decreased by 47%, but the number of AIDS-related deaths increased by 88%. Overall, the number of HIV cases in Indonesia fluctuates, but on an upward trend. Nonetheless, the Indonesian government is committed to helping the world achieve its goal of ending AIDS by 2030.